2014
DOI: 10.1002/eji.201444454
|View full text |Cite
|
Sign up to set email alerts
|

DNGR‐1 is dispensable for CD8+ T‐cell priming during respiratory syncytial virus infection

Abstract: During respiratory syncytial virus (RSV) infection CD8+ T cells both assist in viral clearance and contribute to immunopathology. CD8 + T cells recognize viral peptides presented by dendritic cells (DCs), which can directly present viral antigens when infected or, alternatively, "cross-present" antigens after endocytosis of dead or dying infected cells. Mouse CD8α + and CD103 + DCs excel at cross-presentation, in part because they express the receptor DNGR-1 that detects dead cells by binding to exposed F-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…DNGR-1 is a receptor that can couple detection of dead cells to CD8 + T cell priming 29 , even though it is not, technically, a DC-activating receptor 30 31 . However, we have recently shown that DNGR-1 is dispensable for T cell responses to RSV in mice 32 although it could become non-redundant in the MTM −/− mice, when activation of DCs via PAMPs is absent. Other dead cell-derived mediators that could promote DC activation include heat shock proteins, HMGB1, uric acid, and ATP 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNGR-1 is a receptor that can couple detection of dead cells to CD8 + T cell priming 29 , even though it is not, technically, a DC-activating receptor 30 31 . However, we have recently shown that DNGR-1 is dispensable for T cell responses to RSV in mice 32 although it could become non-redundant in the MTM −/− mice, when activation of DCs via PAMPs is absent. Other dead cell-derived mediators that could promote DC activation include heat shock proteins, HMGB1, uric acid, and ATP 28 .…”
Section: Discussionmentioning
confidence: 99%
“…according to UK home office guidelines. Bronchoalveolar lavage (BAL) and lungs were obtained as described previously 32 . Briefly, BAL was collected by flushing the lungs three times with 1 ml of PBS/0.5 mM EDTA (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the cellular composition of the BAL, cells were transferred onto a microscope slide (Thermo Fisher Scientific) using a Shandon Cytospin 3 centrifuge, and slides were stained with hematoxylin and eosin (H&E; Reagena, Gamidor). Cells were categorized as macrophages, lymphocytes, neutrophils, and eosinophils based on morphology and size under a light microscope (Axio; Carl Zeiss; Durant et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…In some experiments, blood was collected from the tail vein into EDTA-coated Eppendorf tubes and further treated with red blood cell lysis buffer (Sigma–Aldrich) prior to Ab staining. Lungs and female genital tracts (GTs) were harvested from perfused female mice and broncho-alveolar lavage (BAL) fluid was also collected where indicated as described previously [19] .…”
Section: Methodsmentioning
confidence: 99%